Kajian Kekuatan dan Daktilitas Kolom Bertulang - Sumirin, Sumirin (Department of Civil Engineering, Diponegoro University, 2006)
This paper present strength analysis and of ductility of normal concrete column and high quality concrete which confined by lateral reinforcement by comparing made by model’s from Meander-Priestley, Kent-Park, Antonius-Munaf and also Legeron-Paultre. Reinforced Concrete Column with variation of strength concrete and stirrup analysed to use computer program which is its result can be presented visual graphic. Result of analysis indicate that stiffness of concrete confined by among model of Mander-Priestley, Kent-Park, Antonius-Munaf and of Legeron-Paultre its result vary one another if strength concrete fc’ progressively mount. Curve before respon culminate at curve of Moment-Curvature tend differing one another improved of strength concrete fc'. All of model happened degradation of Capacity of Moment at spacing stirrup decrease. In general ductility typicaly not far differ between model of Mander-Priestley, Kent-Park, Antonius-Munaf and of Legeron-Paultre. From is fourth of the model concluded that estimation of ductility and strength moment is tending to highest. Keywords: column, momen-curvature, konfinement model Permalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3935[How to cite: Sumirin, 2006, Kajian Kekuatan dan Daktilitas Kolom Bertulang, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 1, pp. 63-72]